2021
DOI: 10.3390/su13115920
|View full text |Cite
|
Sign up to set email alerts
|

Is Consumer Overchoice a Reason for Decision Paralysis?

Abstract: Time and responses are vital to the process of decision-making. It is a common assumption that having a wide array of options from which to choose is a good thing, but is that truly the case? This research aims to investigate the consumer’s reaction to the increasing number of choices available (which will be referred to as choice overload, or overchoice); more precisely, if it is related to paralysis concerning decision-making. To obtain structured and relevant results, the study is an intergenerational one, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Literature has demonstrated that the problem of these differences is sustained, of interest, and up to date. The importance of education in attaining some sustainable goals in the long run demands the analysis of the differences among groups based on age, level of studies, sex, and background, which are frequently analyzed in the present research [72][73][74].…”
Section: H2 Knowledge Of the Environmental Values (Navs) Has A Signif...mentioning
confidence: 99%
“…Literature has demonstrated that the problem of these differences is sustained, of interest, and up to date. The importance of education in attaining some sustainable goals in the long run demands the analysis of the differences among groups based on age, level of studies, sex, and background, which are frequently analyzed in the present research [72][73][74].…”
Section: H2 Knowledge Of the Environmental Values (Navs) Has A Signif...mentioning
confidence: 99%
“…A túlzott választék a fogyasztókban boldogtalansággal, kimerültséggel járhat, ami döntési bénulás (decision paralysis) kialakulásához vezet. Ez a vásárlási döntés elhalasztásához vezethet, ami nem ideális kimenetel sem a fogyasztó, sem a kereskedő számára (Manolică, Guță, Roman, & Dragăn, 2021). A fogyasztók azonnali döntéshozatalra késztetése céljából a kereskedelmi gyakorlatban éppen ezért számos vásárlásösztönző eszközt alkalmaznak a marketingszakemberek.…”
Section: áBra Az Online Vásárlási Folyamatunclassified
“…Analysis paralysis is most likely where the individual is overloaded with choice and information, rendering them unable to reach a conclusion (Langley, 1995). The phenomenon has predominantly been applied to consumer studies, where it is argued that when faced with an overwhelming number of choices, consumers are crippled by the large number of variables they have to cope with in making a decision (Manolicȃ et al, 2021). Independent of context, many situations requiring the processing of information can be too complicated, causing decision makers to become paralysed by the fear that the consequences of any given alternative could result in an even larger problem (Haupt and Shockley (2018).…”
Section: Analysis Paralysis Eco-fatigue and Travel/ Tourism Consumptionmentioning
confidence: 99%